2019
DOI: 10.1016/j.proci.2018.05.138
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study, under LTC conditions, of ammonia ignition delay with and without hydrogen addition

Abstract: For long-term storage, part of the excess renewable energy can be stored into various fuels, among which ammonia and hydrogen show a high potential. To improve the power-to-fuel-to-power overall efficiency and reduce NOx emissions, the intrinsic properties of Low Temperature Combustion (LTC) engines could be used to convert these carbon-free fuels back into electricity and heat. Yet, ignition delay times for ammonia are not available at relevant LTC conditions. This lack of fundamental kinetic knowledge leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(70 citation statements)
references
References 30 publications
(38 reference statements)
2
67
0
Order By: Relevance
“…Premixed systems are characterized by the equivalence ratio, , defined on the basis of complete combustion of the reactants to carbon dioxide (CO 2 ), water (H 2 O), and nitrogen (N 2 ). Figure 1 shows a comparison of the experimental data obtained by Pochet et al 31 with computational results for ignition delay times in air (with some of the nitrogen replaced by argon to improve compression) of fuel-lean NH 3 with different amounts of H 2 addition. The ignition delay time is defined experimentally as the time between attainment of the maximum compression pressure and the maximum rate of pressure rise in the rapid-compression machine.…”
Section: Comparisons With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Premixed systems are characterized by the equivalence ratio, , defined on the basis of complete combustion of the reactants to carbon dioxide (CO 2 ), water (H 2 O), and nitrogen (N 2 ). Figure 1 shows a comparison of the experimental data obtained by Pochet et al 31 with computational results for ignition delay times in air (with some of the nitrogen replaced by argon to improve compression) of fuel-lean NH 3 with different amounts of H 2 addition. The ignition delay time is defined experimentally as the time between attainment of the maximum compression pressure and the maximum rate of pressure rise in the rapid-compression machine.…”
Section: Comparisons With Experimentsmentioning
confidence: 99%
“…While the rapid-compression machine approximates well conditions of practical interest, shock-tube experi- 31 Open symbols represent the experimental data, solid lines stand for the updated mechanism, and dashed lines are for the previous San Diego mechanism, conventions to be retained in all figures. Solid symbols along each line identify the corresponding H 2 content ments often employ large excesses of argon or helium to improve the fidelity of fundamental data.…”
Section: Ignition Delay Timementioning
confidence: 99%
“…On the other hand, several experimental campaigns carried out in the latest years in less conventional conditions (lower temperatures, high dilution levels and wider pressure ranges) have shown that the fundamental knowledge of ammonia kinetics is still far from complete: the available mechanisms have shown important deviations in the autoignition behavior in diluted conditions, both in hightemperature shock tubes (ST) 27 and low-to intermediatetemperature shock tubes 32 and rapid compression machines (RCM). 33,34 Similarly, flow reactor experiments of pure NH 3 oxidation under atmospheric 35 and high pressure 36 showed that the kinetic models were not always able to reproduce the experimental trends. Da Rocha et al 37 showed the inadequacy of several kinetic mechanisms in predicting the laminar flame speed (LFS) of NH 3 , and most of them were shown to overpredict the actual rates.…”
Section: Introductionmentioning
confidence: 99%
“…To promote the utilization of the ammonia/methane combustion, further studies are still needed to determine the fundamental combustion properties of ammonia‐based fuels. As an essential property of combustion, ignition characteristics studies on ammonia‐based fuels are still limited 29‐31 . Mathieu et al 29 performed ignition delay measurements of ammonia in shock tube under the pressures up to 30 atm and temperature of 1560 to 2455 K. A comprehensive kinetics model was also developed with satisfactory accuracy in prediction of ignition delay time and NOx emission of ammonia.…”
Section: Introductionmentioning
confidence: 99%